Thermal simulation outputs: exploring the concept of patterns in design decision-making. Issue 1 (2nd January 2016) - Tucker, Simon; Bleil de Souza, Clarice
Abstract : This paper describes the ongoing development of a building performance simulation (BPS) knowledge management scheme for design decision-making. This knowledge management scheme is developed with reference to the patterns of Christopher Alexander and colleagues, which describe commonly recurring abstract problems in architectural design together with successful abstract solutions. As such they form a 'repository of knowledge' on architectural design. Patterns have been used in other fields such as software engineering where they also aim at capturing expert knowledge, and their potential to do the same for BPS is explored here. Decision support using simulation is introduced and the concept of patterns described. A pattern structure is developed and some examples given. Interviews with architectural practices investigated whether patterns could support design processes, and the further development of the concept is discussed.